Informal Education as a Method of Young Specialist`s Anxiety Overcoming - Rubel, Nataliia (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2020)
The article shows the effectiveness of informal education assistance as a method of young specialist`s anxiety overcoming study. The sample consisted of 150 people between the ages of 21 and 49, divided into three groups. The first group included 44 people, short-term students, the second group (60 people) – middle-term students, and the third group (46 people) – long-term informal education assistance courses. We used Spilberger-Khanin`s anxiety test to define the level of personal and situational anxiety. To define professional difficulties, we used a half-structured interview and self-report. Short-term educational programs students have a low level of personal anxiety and middle-level situational anxiety, which changed slightly after the educational program (the difference is insignificant). The members of this group, as usual, have about 2 years of work experience and apply for academic help on specific professional issues. Middle-term educational programs participants mostly do not have work experience are somewhat confused about their professional specialization (for example: «I want to work with children or with adults, I do not know», «I want certain instruments, but I am not sure if I need them»), do not see the point of an in-depth study that or another theme. At the beginning of the course, they have a high level of personal and situational anxiety. They try to get the basics for the future work, quite quickly overcome the confusion, in studying situational anxiety of this group decreased with a significant difference (p < 0.05). Examined members of long-term educational programs have a middle level of individual and situational anxiety at the beginning. They try to understand many professional issues and feel tension and confusion. Situational anxiety in this group decreased with a significant difference (p < 0.05) in the process of studying. Members of this group feel the necessity to set goals and to plan their professional activity (for example: «I do not know where to start», «I do not understand why we need to do this», «I need consistency in work»), that is why they choose programs with a significant substance and content. The proposed system of educational assistance is based on the problem-oriented approach. We have identified the lack of beginner’s practical skills, tools, and professional activity techniques as the main problem that leads to difficulties during a professional crisis. We suppose that overcoming this deficit affects changes in specialists’ activity quality and their psycho-emotional condition. Our study results suggest that the proposed program of informal education has a positive effect on overcoming anxiety during the professional development crisis.